Analisis Kelayakan Finansial Usaha Agroindustri Kerupuk Ikan Tenggiri di Kecamatan Karimun Kepulauan Riau (Studi Kasus Kerupuk Bona) - Rizki, Rini Pradipta; Yusmini, Yusmini; Edwina, Susy (Universitas Galuh, 2025)
Fish Crackers business is a business that has great potential to be developed in Indonesia, this is due to the abundant fish catch. One of the fish that is quite widely processed into crackers is mackerel. This study aims to analyze the financial feasibility and sensitivity to changes in input prices and production levels of the Bona Tenggiri Fish Crackers Agroindustry in Karimun District, Karimun Regency, Riau Islands. The research method used is the case study method. The data used are primary data and secondary data. Informants in this study were Bona Agroindustry business owners and 2 workers. Data analysis of investment criteria used is Net Present Value (NPV), Internal Rate of Return (IRR), and Net Benefit Cost Ratio (Net B/C). The results showed: Bona Agroindustry is feasible because it has a positive NPV value of Rp.2.163.103.068, the IRR value is greater than the Social Opportunity Cost of Capital (SOCC) which is 46%, and the Net B/C value is greater than zero which is 5,94. Based on the results of the sensitivity analysis conducted on the 15,38% increase in mackerel input prices, 30,36% increase in cooking oil input prices and a 10% decrease in production, it shows that the Bona Agroindustry business is still feasible to run or develop.